Ethical human resource management mitigates the positive association between illegitimate tasks and employee unethical behaviour. Issue 2 (24th December 2021) - Chen, Silu; Liu, Wenxing; Zhang, Guanglei; Wang, Hai‐Jiang
Abstract: Drawing on social cognitive theory and social information processing theory, we developed a moderated mediation model in which moral disengagement was theorised as a unique mechanism to explain why employees engage in unethical behaviours after performing illegitimate tasks. Ethical human resource management (HRM) was proposed as a boundary condition that influences this mechanism. We tested the model using time‐lagged supervisor–subordinate matched data. The results showed that moral disengagement mediated the relationship between illegitimate tasks and unethical behaviours, and that this relationship was weaker when ethical HRM was perceived to be high level rather than low level. Thus, our hypotheses were supported. The theoretical and practical implications of these findings are discussed.